Linewidth control by overexposure in laser lithography - Yiyong, Liang; Guoguang, Yang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In micro-electronic and micro-optical manufacturing, especially in the fabrication of linewidth-variation-sensitive devices, we sometimes care getting stable or precise linewidth rather than creating a thinner line. In laser lithography, the energy distribution of a focused laser spot is of Gaussian form, and the modification of an exposure dose or exposure threshold will cause linewidth variation. If the peak of energy distribution of a laser spot is a little higher than the exposure threshold of a photoresist layer, the produced linewidth may be small but unstable, and if the peak is considerably higher than the threshold, in other words in the case of overexposure, the linewidth will be relatively stable. The test was carried out in a polar laser lithographic system through a continuously changing exposure dose. The experimental result shows that the dose-induced linewidth variation velocity is different under a variant exposure dose. The higher the exposure dose, the lower the linewidth variation velocity.
Optica Applicata, Vol. 38, 2008, nr 2, s. 399-404
Keywords: optyka; linewidth; overexposure; laser lithography